Incidence of Hospitalisation and Emergency Department Visits for Pneumococcal Disease in Children, Adolescents, and Adults in Liguria, Italy: A Retrospective Analysis from 2012–2018 - Matteo Astengo; Chiara Paganino; Daniela Amicizia; Laura Sticchi; Andrea Orsi; Giancarlo Icardi; Maria Francesca Piazza; Salini Mohanty; Francesca Senese; Gian Marco Prandi; Filippo Ansaldi (Vaccines, 2022)
Streptococcus pneumoniae infection is responsible for significant morbidity and mortality, particularly in young children and older adults. The aim of this study was to investigate the incidence of hospitalisation and emergency department (ED) visits in relation to episodes of pneumococcal disease (PD) following the introduction of pneumococcal conjugate vaccines (PCVs) into the Liguria region of Italy. Between 2012 and 2018, episodes of all-cause pneumonia (80,152), pneumococcal-specific pneumonia (1254), unspecified pneumonia (66,293), acute otitis media (AOM; 17,040), and invasive PD (IPD; 1788) were identified from in-patient claims, ED and hospital discharge records, and the Liguria Chronic Condition Data Warehouse. In children < 15 years of age, pneumococcal pneumonia-related hospitalisations decreased from 35 to 13 per 100,000 person-years during the study period (p < 0.001); this decrease is potentially related to PCV use in children. All-cause pneumonia hospitalisations remained stable, whereas IPD hospitalisations increased and AOM hospitalisations decreased. In adults, hospitalisations for all-cause pneumonia increased from 5.00 to 7.50 per 1000 person-years (+50%; p < 0.001). Pneumococcal and unspecified pneumonia hospital admissions increased significantly during the study period, considerably affecting those ≥ 65 years of age. IPD hospitalisations varied across all age groups, but a significant change was not observed. Despite pneumococcal vaccination, substantial burden remains for PD in children and adults in Liguria, Italy.